THE DEVICE OF LOW-INTENSIVE INFLUENCE BY INFRARED RADIATION ON THE HUMAN BODY FOR RESTORATION OF HIS FUNCTIONAL STATE - A. N. Osipov; M. H. Tkhostov; M. M. Mezhennaya; N. I. Stetyukevich; V. F. Shevtsov; V. A. Kulchitsky; D. A. Kotov; N. S. Davydova; V. Yu. Drapeza (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The device has been developed to restore the human body functional state. The device provides the effect of low intensity infrared (IR) radiation. It is a closed cabin with door, air ventilation system, IR sources, reflectors to protect a person's head, sensors of temperature and humidity, timer. Infrared cabin increases the efficiency of IR heating of human body through the use of the primarily near infrared range emitters. The advantages are also the lack of excessive heat load on the cardiovascular system and minimize energy costs.